Perkembangan Gereja Katedral Santo Yosep Kota Pontianak Tahun 1909 - 1940 - Julianda*, Rizky; Firmansyah, Andang; Mirzachaerulsyah, Edwin (Universitas Syiah Kuala, 2024)
The research was conducted with the aim of knowing the development of St. Yosep Cathedral Church of Pontianak City from 1909-1940. The research method used is the historical research method which consists of a. Topic Selection, b. Heuristics c. Verification, d. Interpretation, e. Historiography. The results of this study indicate that the entry of Catholicism into West Kalimantan in the early 20th century, especially in Pontianak which in 1909 was made a mission center and missionary center, the number of missionaries who came made many mission works established in Pontianak. This greatly influenced the Catholics and the people in Kalimantan especially in Pontianak thanks to Msgr. Pacificus Bos, O.F.M. Cap, and Msgr. Tarcisius Henricus Josephus van Valenberg, O.F.M. Cap. These two men were the pillars of the missionary works built in Pontianak, the most important of which was the Cathedral Church of St. Yosep Pontianak. This church is used as a mission center for missionaries, besides the church there is also Antonius Hospital and schools founded by the Pontianak Brothers School Foundation until now the results of this mission work are still growing and are still active until now, the mission works made by these missionaries greatly influenced the development of Catholics in Kalimantan, especially in Pontianak. In 1938 the Catholics reached 10,000 people but unfortunately in the 1940s the mission work stopped due to Japanese colonization, this made the development of Catholics not develop.